Pengaruh Iklan, Harga dan Keunikan Asosiasi Merek terhadap Omzet Penjualan - Muhammad Nur Huda (Universitas Islam Kadiri, 2018)
The influence of advertisement, price and uniqueness of brand association is among several factors that influence sales turnover and it is very important to know how much influence to sales turnover of dove soap in PT. Sekar Nusa Baruna. By knowing the relationship, the company can estimate the consumer's response to advertisement, price and uniqueness of the brand association that has been given so that it can make a plan and improve the sales turnover in the future. Sampling technique using accindental sampling technique and samples taken are community of kediri shopping at official store of PT. Sekar Nusa Baruna Kediri. Data obtained through questionnaires and interviews, the results obtained show that advertising variables affect the most significant among the price variables and uniqueness of the brand association of sales turnover with a significant value of 0.00. The results of the research analysis simultaneously known the influence of the three variables studied by 51.9% of sales turnover.